2005
DOI: 10.1158/0008-5472.can-05-0271
|View full text |Cite
|
Sign up to set email alerts
|

Calcium/Calmodulin-Dependent Kinase I and Calcium/Calmodulin-Dependent Kinase Kinase Participate in the Control of Cell Cycle Progression in MCF-7 Human Breast Cancer Cells

Abstract: Calcium is universally required for cell growth and proliferation. Calmodulin is the main intracellular receptor for calcium. Although calcium and calmodulin are well known to be required for cell cycle regulation, the target pathways for their action remain poorly defined. Potential targets include the calcium/calmodulin-dependent kinases (CaM-K). The aim of this study was to determine the role of the CaM-Ks on cell proliferation and progress through the cell cycle in breast cancer cells. CaM-KI inhibition wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 47 publications
0
60
1
Order By: Relevance
“…Combined with these recent findings, our data are suggestive of the possibility that nuclear PTEN induces G 0 -G 1 cell cycle arrest by Ca 2+ signaling-regulated nuclear import. Ca 2+ signaling is known to regulate G 1 -S progression of the cell cycle through promoting phospholipase C/protein kinase C/MAPK and calmodulin (CaM)/ CaM-dependent kinase (CaM-K) kinase/CaM-K pathways (23)(24)(25)(26). Therefore, it is reasonable to postulate that Ca 2+ signaling is also regulating nuclear entry of PTEN, resulting in modulation of G 1 cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with these recent findings, our data are suggestive of the possibility that nuclear PTEN induces G 0 -G 1 cell cycle arrest by Ca 2+ signaling-regulated nuclear import. Ca 2+ signaling is known to regulate G 1 -S progression of the cell cycle through promoting phospholipase C/protein kinase C/MAPK and calmodulin (CaM)/ CaM-dependent kinase (CaM-K) kinase/CaM-K pathways (23)(24)(25)(26). Therefore, it is reasonable to postulate that Ca 2+ signaling is also regulating nuclear entry of PTEN, resulting in modulation of G 1 cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Since these inhibitors disrupt CaMKI and CaMKIV activities [32,33], and may therefore affect CKLiK activities in neutrophils, we tested whether KN-93 and the recently identified CaMKKα inhibitor STO-609 also affect the growth or functional responses of our cell lines. In agreement with previous studies on human leukemic cell lines, KN93 inhibited the growth of both EPRO and SCF ER-Hoxb8 cells in a dose dependent fashion (Fig.…”
Section: Effects Of Camk Inhibitors On Murine Neutrophil Growth Diffmentioning
confidence: 99%
“…KN-93, as a membrane permeant compound of CaMK Ⅱ-selective inhibitor, can intensively prevent CaMK-Ⅱ activation by antagonizing CaM binding [10] , and has been used in functional studies on living cells. In contrast to KN-93, KN-92 is a congener of KN-93 without CaM kinase inhibitory activity and has been used as an experimental control [11] . It was reported that KN-93 not only suppresses CaMKⅡ activity but is a strong inhibitor of cell proliferation [12] .…”
Section: Introductionmentioning
confidence: 99%